The Correlation of Guided Inquiry Model with SETS Approach on Students' Critical Thinking Skills - R. Melisa Nelvita Sari; Siti Suryaningsih; Luki Yunita (EDUSAINS, 2018)
KORELASI MODEL INKUIRI TERBIMBING BERPENDEKATAN SETS TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA AbstractCritical thinking skills in chemistry subject is still low. Teacher-centered learning is one of the causes of low critical thinking skills. The objective of this study was to investigate the correlation of guided inquiry learning model with the Science, Environment, Technology and Society (SETS) approach on students’ critical thinking skills at chemical equilibrium material. The research method was Quasi Experiment with Nonequivalent Control Group Design, and the samples were taken using purposive sampling. The samples consisted of 36 students in the control and the experimental classes. The research instrument consisted of 12-item essay test which represented 11 indicators of critical thinking skill. Data analysis was performed using the Independent Sample T-test through SPSS 22 version. The results of hypothesis testing showed a correlation of the use of guided inquiry model with SETS approach on students' critical thinking skills in the experimental class with sig values <0.05. The percentage result of the posttest data showed an increase in critical thinking skills of students in the experimental class. The conclusion of this study is that the use of guided inquiry model with SETS approach can improve students' critical thinking skills. The highest critical thinking skills indicator in the experimental class is inducing and judging inductions, while the lowest indicator is observing and judging observation reports.AbstrakKeterampilan berpikir kritis pada mata pelajaran kimia masih rendah. Pembelajaran yang berpusat pada  guru adalah salah satu penyebab rendahnya keterampilan berpikir kritis. Tujuan penelitian untuk mengetahui korelasi model pembelajaran inkuiri terbimbing berpendekatan Science, Environment, Technology, dan Society (SETS) terhadap keterampilan berpikir kritis siswa pada materi kesetimbangan kimia. Metode penelitian adalah Quasi Experiment dengan desain Nonequivalent Control Group Design, dan teknik yaitu purposive sampling. Sampel penelitian sebanyak masing-masing 36 orang pada kelas kontrol dan eksperimen. Instrumen penelitian berupa tes esai sebanyak 12 butir soal yang mewakili 11 indikator keterampilan berpikir kritis. Analisis data menggunakan Independent Sample T-test melalui SPSS versi 22. Hasil uji hipotesis menunjukkan adanya korelasi penggunaan model inkuiri terbimbing berpendekatan SETS terhadap keterampilan berpikir kritis siswa kelas eksperimen dengan nilai sig. < 0,05. Hasil persentase data posttest menunjukkan adanya peningkatan keterampilan berpikir kritis siswa pada kelas eksperimen. Kesimpulan dari penelitian ini bahwa penggunaan model inkuiri terbimbing berpendekatan SETS mampu meningkatkan keterampilan berpikir kritis siswa. Indikator keterampilan berpikir kritis tertinggi di kelas eksperimen adalah membuat induksi dan mempertimbangkan hasil induksi dan indikator terendah adalah mengobservasi dan mempertimbangkan hasil observasi.